Matrix effect on phytochemical bioaccessibility. The case of organosulfur compounds in garlic preparations. (January 2021) - Torres-Palazzolo, Carolina A.; Ramírez, Daniela A.; Beretta, Vanesa H.; Camargo, Alejandra B.
Abstract: Phytochemicals are dietary compounds considered lifespan-essentials. Their beneficial effects strongly depend on their bioaccessible quantities, in turn determined by food matrix components. Organosulfur compounds (OSCs) are renowned phytochemicals responsible for garlic health-effects. Currently, garlic matrix role in OSCs bioaccessibility has not been studied. Furthermore, the digestive behavior of isolated OSCs added to garlic preparations is unknown. In order to decipher these questions, different garlic matrices were subjected to in vitro digestion. Our findings demonstrate that garlic matrix impacts significantly on OSCs digestive performance. Therefore, digestive stability and bioaccessibility varied with the garlic preparation form. Powdered garlic, in fresh and stir-fried form, presented the highest stability and bioaccessibility values because matrix components suspended in digestive fluids protected OSCs during digestion. Hence, garlic powder would be suitable for OSCs dietary incorporation and functional food design. On the other hand, naturally occurring OSCs were more stable than isolated OSCs added to garlic samples. This behavior can be explained by a more deepen interaction of endogenous compounds with the matrix components and their location inside the vegetable structure. Therefore, OSCs addition procedures in food matrices should be carefully designed to optimize the phytochemical bioefficacy. Highlights: Garlic matrix components in digestive fluids protected OSCs during digestion. Naturally occurring OSCs are more stable than added OSCs during digestion. OSCs added to foods should be protected from gastrointestinal environment. Garlic powder is a suitable preparation for OSCs dietary incorporation.